Mechanical Mastication of Utah Juniper Encroaching Sagebrush Steppe Increases Inorganic Soil N - Kert R. Young; Bruce A. Roundy; Dennis L. Eggett (Applied and Environmental Soil Science)
Juniper (Juniperus spp.) has encroached on millions of hectares of sagebrush (Artemisia spp.) steppe. Juniper mechanical mastication increases cover of understory species but could increase resource availability and subsequently invasive plant species. We quantified the effects of juniper mastication on soil resource availability by comparing total C, total N, C : N ratio, Olsen extractable P, sulfate S, and pH using soil samples and inorganic N (NO3-+NH4+) using ion exchange membranes. We compared resource availability in paired masticated and untreated areas in three juniper-dominated sagebrush and bunchgrass ecosystems in the Utah portion of the Great Basin. Inorganic N was 4.7 times higher in masticated than in untreated areas across seasons (P<0.001). Within masticated areas, tree mounds of juniper leaf scales and twigs served as resource islands with 1.9 times higher inorganic N and total C, and 2.8 times higher total N than bare interspaces across seasons (P<0.01). Bare interspaces had 3.0–3.4 times higher inorganic N than interspaces covered with masticated trees during late-summer through winter (P<0.01). Soil fertility changes associated with mastication were not considered sufficient to favor establishment of annual over perennial grasses, and we expect both to increase in cover following juniper mastication.